2021
DOI: 10.1097/mou.0000000000000916
|View full text |Cite
|
Sign up to set email alerts
|

The place of robotic-assisted laparoscopy for BPO surgical management in 2021

Abstract: Purpose of review Robot-assisted laparoscopic simple prostatectomy (RASP) is being used increasingly for the surgical treatment of benign prostatic obstruction (BPO). Our purpose is to review the main outcomes of RASP for the management of BPO. Recent findings A computerised bibliographic search of Medline was performed for articles that included detailed results of RASP, published over the past 2 years. Although RASP seems to be associated with better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Several different surgical techniques for RASP have been reported [5] , including a transperitoneal or extraperitoneal approach and a transvesical or extravesical anterior approach to the adenoma. Leslie et al [6] reported a posterior transvesical approach involving transversal incision of the bladder dome without dropping it.…”
Section: Introductionmentioning
confidence: 99%
“…Several different surgical techniques for RASP have been reported [5] , including a transperitoneal or extraperitoneal approach and a transvesical or extravesical anterior approach to the adenoma. Leslie et al [6] reported a posterior transvesical approach involving transversal incision of the bladder dome without dropping it.…”
Section: Introductionmentioning
confidence: 99%